Majas pada Antologi Cerita Rakyat Daerah Istimewa Yogyakarta Sebagai Bahan Ajar Menulis Puisi - Purba, Herlina; Wardana, Deni; Widjojoko, Widjojoko (Didaktika, 2022)
Stylistics is one of the most important elements in shaping poetry. This study intends to analyze the language style in the Anthology of Folklore of the Special Region of Yogyakarta as an alternative to making teaching materials for writing poetry in grade IV elementary school. This research includes qualitative research using the content analysis method because this research analyzes the language style in the folklore book, the analysis is carried out by reducing the data, describing the data, and drawing conclusions. Based on the results of the study, 112 sentences were found that used the language style in this book, including the comparative language style totaling 35 data, the conflicting language style totaling 43 data, the linking language style totaling 28 data, the linking language style totaling 6 data. The language style contained in the storybook except for the metaphorical language style can be used as learning material for writing poetry in grade IV elementary school. Learning materials are made in the form of handouts containing material on writing poems, language styles for teacher's handles and student worksheets containing language style exercises and writing poems. This can be a reference for teachers to utilize authentic works in learning Indonesian about poem writing